Progress and Current Status of Treatment for Lower Limb Varicose Veins - Li, Xinyang; Wu, Shile (Journal of Contemporary Medical Practice, 2024)
Varicose veins of lower extremities are common venous diseases of lower extremities in clinic [1]. The total number of patients with varicose veins of lower extremities in China has exceeded 100 million, and the incidence rate is about 15% [2]. Therefore, there is a huge number of illnesses and a demand for surgical treatment. At present, the main treatment options for lower limb varicose veins include conservative treatment and surgical treatment. Surgical treatment methods include traditional surgery and minimally invasive surgery. The high ligation and stripping of the great saphenous vein has always been the gold standard for the treatment of lower limb varicose veins. This method is technically mature and clinically effective, but it is a destructive surgery that uses a stripping device to forcefully pull. Therefore, the intraoperative trauma is large, the amount of bleeding is high, and a series of postoperative complications such as hidden nerve damage, subcutaneous congestion, incision bleeding, deep vein thrombosis, etc. are prone to occur. With the increasing demand for skin aesthetics and reducing postoperative complications, minimally invasive surgery has gradually been applied to the treatment of lower limb varicose veins, such as intracavitary laser ablation, intracavitary radiofrequency ablation, Tri Vex minimally invasive rotary cutting, hemodynamic correction, etc. [3]. This article provides a review of the current main treatment methods for lower limb varicose veins, in order to further understand and master the principles and application scope of each treatment method, and to better select personalized treatment plans for varicose vein patients in the future.